To Construction of Expendable Hydroelectric Power Station Characteristics and Their Timely Correction - V. Kh. Nasibov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper provides a technique of analytical construction of expendable characteristics and characteristics of a relative gain of water charge at a hydroelectric power station. Planning method and regression analysis have been applied for the construction of these characteristics.